Implementasi Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pendidikan Provinsi Sulawesi Selatan - Ayu Ashari; Andi Irwan; Jumaidah Jumaidah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Ayu Ashari, in 2024 Implementation of Work Discipline on Employee Performance at the South Sulawesi Provincial Education Office, Management Study Program Thesis at the Indonesian Educational Institution College of Management Science (STIM-LPI) Makassar. Supervised by Dr. Andi Irwan, S.E., M.Si. and Jumaidah, S. Sos., M. Si. This research aims to determine the implementation of work discipline on employee performance at the South Sulawesi Provincial Education Office. The method used in this research is a quantitative method with the number of respondents being 55 employees who were sampled using a sampling technique, namely the sloving technique, where the data collection technique uses a questionnaire. The analysis used in this research is a simple linear regression test. The results of partial testing of work discipline variables on employee performance have a significant influence on employee performance as proven based on partial test results with a significant value of f 0.001 < 0.05.